Blood‐based circulating tumor DNA mutations as a diagnostic and prognostic biomarker for lung cancer. Issue 8 (30th January 2020) - Leung, Maria; Freidin, Maxim B.; Freydina, Daria V.; Von Crease, Charlotte; De Sousa, Paulo; Barbosa, Monica T.; Nicholson, Andrew G.; Lim, Eric
Abstract : Background: The objectives of the current study were to develop an initial blood‐based circulating tumor DNA (ctDNA) gene signature and to validate the clinical test performance in patients with early primary and secondary lung cancer. Methods: Between January 2009 and October 2014, a total of 211 patients with known or suspected lung cancer donated their blood prior to surgery and were followed up to May 2018. ctDNA was extracted from plasma and from corresponding formalin‐fixed, paraffin‐embedded tissues. The blood was analyzed in a blinded manner and pathology reports were issued that were blinded to the blood test results. The reference standard was histopathology confirmed cancer in the resected surgical specimens as reported according to World Health Organization criteria and staged using the eighth edition of the TNM Classification of Malignant Tumors criteria. Results: Of 211 consenting patients, 19 (9.0%) were excluded, leaving 192 participants, consisting of 95 men (49%) and with a mean age of 63 years (SD, 15 years). The clinical test performance for the blood‐based diagnostic signature demonstrated a sensitivity of 75% (95% CI, 67%‐81%), specificity of 89% (95% CI, 70%‐98%), positive predictive value of 98% (95% CI, 93%‐100%), and negative predictive value of 35% (95% CI, 24%‐48%) when compared with conventional clinical histopathology reporting of the resected tissue. Conclusions: The results of the current study suggested that blood‐based ctDNA analysis of cancer mutations is a specific, noninvasive test for the diagnosis of cancer. Abstract : The results of the current study demonstrate good concordance between circulating tumor DNA (ctDNA) in blood and mutations detected in formalin‐fixed, paraffin‐embedded samples. The findings suggest that the blood‐based ctDNA analysis of cancer mutations is a specific, noninvasive test.